PENGARUH PUPUK ORGANIK DAN ANORGANIK ZA DAN SP 36 TERHADAP HASIL DAN MUTU TEMBAKAU TEMANGGUNG PADA TANAH ANDISOL - DJAJADI DJAJADI; M. SHOLEH; NUNUNG SUDIBYO (Jurnal Penelitian Tanaman Industri, 2002)
Effect of organic (biogrcen) and inorganic fetilizers (ammonium sulphate and SP36) on the yield and quality of the temanggung tobacco in andosol soil was studied at Galapansari - Temanggung, from Februai to December 2001. The organic and inorganic fetilizers were formulated in 10 packages, namely : (1) 570 kg ammonium sulphate (AS) ♦ 100 kg SP36; (2) the recommended rate for temanggung tobacco (20 000 kg stable manure 500 kg AS + 100 kg SP36; (3) 5 000 kg organic fetilizer (OF); (4) 7 500 kg OF; (5) 8 500 kg OF; (6) 10 000 kg OF; (7) 12 500 kg OF; (8) 14 500 kg OF; (9) 7 500 kg OF + 3 500 kg sUble manure (SM); (10) 7 500 kg OF + 4 500 kg SM. All the rates of fetilizers were based on one hectare planted area (16 500 plants) The expeiment was designed as a randomized block in four replicates. Results showed that organic fertilizer waa more effective than stable manure in improving die growth, yield and quality of temanggung tobacco. A the rate of 5 000 kg was sufficient to produce high ( 6 313 kg fresh or 800 kg sliced died leaves), grade index (51.68) and crop index (55.31). Key words : Organic fetilizer, ammonium sulfate, SP36, temanggung tobacco, andisol